Perancangan Pos Pengelolaan Kas sebagai Sinkronisasi Pencatatan Kas pada Rumah Sakit XXX - Maudy Shinta Maychella; Tri Hesti Utaminingtyas; Ratna Anggraini (Jurnal Akuntansi, Perpajakan dan Auditing, 2026)
This project aimed to design a Cash Management Standard Operating Procedure (SOP), a cash inspection report format, and a bank reconciliation format at Hospital XXX. The project addressed issues related to cash management procedures and the lack of supporting documents for cash inspection and bank reconciliation. Data were collected through interviews, observations, and documentation review and analysed using the PIECES framework, while the ADDIE methodology was applied through the Analysis, Design, and Development phases. The findings indicated the need for standardized guidelines and supporting documents to improve the consistency of cash management practices and documentation processes. Based on these findings, a Cash Management SOP, a cash inspection report format, and a bank reconciliation format were developed in accordance with the hospital’s operational conditions.